Laws of attraction [videorecording (DVD)] - Howitt, Peter, 1957-; Brosnan, Pierce; Moore, Julianne; Sheen, Michael; Posey, Parker, 1968-; Fisher, Frances, 1952-; Dunn, Nora, 1952- (New Line Home Entertainment ; Distributed by Warner Home Video, 2004)
Though equally respected in their field, divorce lawyers Audrey and Daniel are opposites inside and out of the courtroom. Audrey is meticulous and by the book, while Daniel relies on personality and luck to get by. Neither have lost a case and neither intends to now, but a celebrity power couple gone wrong will end one of their winning streaks. The divorce settlement hinges on an old Irish castle. The two race to Ireland where after an Irish festival the two lawyers wake up married. Now the mismatched lawyers have to contemplate how to go about their client's divorce hearings as man and wife.